CRITICAL THINKING AS THE BASIS OF MODERN EDUCATIONAL APPROACHES IN THE FORMATION OF STUDENT PERSONALITY - Horban, Oleksander; Fediuk, Vladyslava (Educological discourse, 2021)
The article postulates that the formation of critical thinking in the individual is a significant challenge of the modern education system, which should offer the latest methodology for personal development of relevant skills to acquire new knowledge and critically evaluate various information flows under the influence of modern man. It is argued that the formation of a strong, conscious personality of the student is identical to the formation of a conscious citizen, which is actually aimed at the New Ukrainian School. First of all, it is expressed in the direction of the development of logic and critical as well as creative thinking. All these three important areas of the learning process contribute to the student's self-reflection and the formation of his personal life position. It is noted that today the public inquiry requires the skills to independently analyze information, to constantly conduct search activities. Learning ceases to be memorization, it appears as a conversation with the teacher, which leads to qualitatively new judgments. That is, modern learning is a triad: search, direct conversation and judgment. Assertive behavior is suggested as the optimal, most constructive way of interpersonal interaction in the learning process. In addition, the personality is formed on the principles of assertiveness, which has critical thinking, expresses its own "I", much less likely to be manipulative. It is concluded that the development of critical thinking is not just an integral part of the modern educational process. The student's ability to think critically, to express his own opinion, unbiased position, is a necessary learning outcome that allows modern man to form a reality-appropriate type of worldview.